Картографирование иранских языков Aфганистана и Пакистана - Коряков, Ю. Б. (ИАЭ)
Данная работа посвящена теоретическим и практическим вопросам создания карт иранских языков, в частности языков Афганистана и Пакистана. В начале мы касаемся общих вопросов и методик создания языковых карт. Далее рассматривается текущая ситуация с языковыми картами этого региона. Затем подробно обсуждаются процесс создания карт, специально сделанных для данного издания, с освещением регионов распространения языков парачи, ормури, хазара. This work is concerned with the theoretical and practical issues of creating maps of Iranian languages, in particular the languages of Afghanistan and Pakistan. We begin by touching on general issues and techniques for creating language maps, before going on to consider the current situation regarding the language maps of this region. Finally, the process of creating maps made specifically for this publication is discussed in detail, with coverage of the regions where Parachi, Ormuri, and Hazaragi are spoken.
Keywords: Языкознание